1996
DOI: 10.1091/mbc.7.12.2019
|View full text |Cite
|
Sign up to set email alerts
|

Distinct cellular locations of the syntaxin family of proteins in rat pancreatic acinar cells.

Abstract: Syntaxins are cytoplasmically oriented integral membrane soluble NEM-sensitive factor receptors (SNAREs; soluble NEM-sensitive factor attachment protein receptors) thought to serve as targets for the assembly of protein complexes important in regulating membrane fusion. The SNARE hypothesis predicts that the fidelity of vesicle traffic is controlled in part by the correct recognition of vesicle SNAREs with their cognate target SNARE partner. Here, we show that in the exocrine acinar cell of the pancreas, multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
160
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(175 citation statements)
references
References 29 publications
14
160
1
Order By: Relevance
“…Alternatively, syntaxin 3 may participate in fusion among intracellular vesicles. Consistent with this possibility, syntaxin 3 (but not coexpressed syntaxin 2 or 4) has been localized to zymogen granules in pancreatic acinar cells (Gaisano et al, 1996), recycling tubulovesicles in gastric parietal cells (Bennett, manuscript in preparation) and secretory granules in eosinophils (Bennett, unpublished data). Recent data indicate that under certain circumstances, NSF acts solely on transport vesicles, prior to docking or fusion of these vesicles with their target (Mayer et al, 1996;Steel et al, 1996).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Alternatively, syntaxin 3 may participate in fusion among intracellular vesicles. Consistent with this possibility, syntaxin 3 (but not coexpressed syntaxin 2 or 4) has been localized to zymogen granules in pancreatic acinar cells (Gaisano et al, 1996), recycling tubulovesicles in gastric parietal cells (Bennett, manuscript in preparation) and secretory granules in eosinophils (Bennett, unpublished data). Recent data indicate that under certain circumstances, NSF acts solely on transport vesicles, prior to docking or fusion of these vesicles with their target (Mayer et al, 1996;Steel et al, 1996).…”
Section: Discussionmentioning
confidence: 72%
“…All syntaxin antibodies were affinity purified before use. All syntaxin antibodies were isotype specific, except for the syntaxin 2 antibody which showed a weak crossreactivity with syntaxin 1 by Western blot (Gaisano et al, 1996). Fluorescein isothiocyanate-or Texas Red-conjugated secondary antibodies were purchased from Jackson ImmunoResearch Laboratories (West Grove, PA).…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…Syn-3-overexpressing cells showed that the number of no-dock newcomer SGs undergoing exocytosis increased by 98% and 164% in first (17.13±3.62 vs control 8.66±1. 19) and second phases (24.60±5.92 vs control 9.32 ±2.03), respectively. Short-dock newcomer SGs in Syn-3-overexpressing cells were increased, but mainly in the first phase (6.13±0.61 vs control 2.45±0.45) (Fig.…”
Section: Syn-3 Is a T-snare On Sgsmentioning
confidence: 87%
“…In retinal cells, SYN-3 is produced in ribbon synapses but its role in neurotransmitter release remains unknown [16,17]. In pancreatic acinar cells [18], SYN-3 was localised to zymogen granule membrane [19] and complexed with VAMP8 to mediate SG-SG fusion [20].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies of recombinant proteins indeed demonstrated stable binding of VAMP-2, SNAP-23, and syntaxin-4 (22), raising the possibility that a complex of VAMP-2/ SNAP-23/syntaxin-4 could mediate basolateral exocytosis of digestive enzymes within the pancreas. Non-neuronal Munc18 isoforms were also identified, including Munc18b and Munc18c (21)(22)(23)(24)(25)(26). Munc18c binds to syntaxin-4 and blocks its binding to SNAP-23 and VAMP-2 (24,25), and overexpression of Munc18c in adipocytes inhibits insulin-mediated GLUT-4 translocation to the plasma membrane and glucose transport (26).…”
mentioning
confidence: 99%